Death of a reserve currency - Stephen Quinn; William Roberds (Federal Reserve Bank of Atlanta, 2014)
The Dutch bank florin was the dominant currency in Europe during much of the 17th and 18th centuries. The florin, a fiat money, was managed by an early central bank, the Bank of Amsterdam. Using a new reconstruction of the Bank of Amsterdam's balance sheet, we analyze the florin's loss of reserve currency status during the period 1781-92. The reconstruction shows that by 1784, accommodative policies rendered the Bank of Amsterdam "policy insolvent," meaning that its net worth would have been negative under continuation of its policy objectives. Policy insolvency coincided with the Bank of Amsterdam's loss of control over the value of its money.
Keywords: E58; F33; N13; 330; central banks; reserve currency; policy insolvency